Adoção da agricultura de precisão na Amazônia: estudo de caso na região cone sul do estado de Rondônia - Batista, Jessé Alves (2016)
During the last years, the application of Precision Agriculture (PA) has been a research object worldwide, and the understanding of the factors related to it becomes crucial for the development of strategies that can meet the needs of dissemination and use of such technologies. This work's objective was to identify the level of PA tools adoption in the south corner of Rondonia, a region that produces soy and corn, it the Brazilian Amazon, as well as the intention to contribute for the state of the art use of these technologies in Brazil. Data gathering was done through applying a questionnaire on 37 PA adopting farmers in this region. The statistical processing of the data was based in two methodologies, Descriptive Statistics, wich displayed percentual, average, and standard diversion. And Matching Analysis, for variable matchings. Intending to compare the indexes of PA adoption in Rondonia to the indexes of adoption in other Brazilian regions where it has been studied, 5% significance intervals of Confidence Intervals (CI) were raised, and hypothesis tests to correlate different populations were applied. The results pointed that PA in Rondonia finds itself at initial adoption phase, being the main restrictive factors to adoption the machinery high cost and the post sale technical assistance low service quality. The automatic pilot, the soil geo-referenced sampling, the fertility map confection and soil correlation at variable rate were the most used tools in the studied region, due to have displayed similar indexes compared to other Brazilian regions. The harvester with yield sensor was the most found PA machine on farms, being the harvest mapping through the productivity map pointed as the next service to be adopted in Rondonia. PA shows great use potential in the region, especially to most of the largely disseminated tools in Brazil, once they are already present in Rondonia's farming activities, added to the expected Rondonian farmers intention of intensifying its use.